Mirror algorithm for computing π\pi and ee – does it hint on some connection between them?

Benoit Cloitre offered two ‘mirror sequences’, which allow to compute π and e in similar ways:






\lim_{n \to \infty} \frac{2n}{v_n^2}=\pi

The formulation and the proof can be seen here.

What do you think – is it just a coincidence or is there some deeper meaning in this mirror algorithm about the connection of two constants?

By @EricStucky in the comment, the better question:

Is there any connection between e and π which is essentially different than Euler’s formula?

Of course, I expect an answer related to my own question about this ‘mirror sequence’

If, on the other hand, someone shows a clear relation between this sequence and Euler’s formula, that’s fine too


Both the limits can be evaluated in a more general scenario where you put constants a and b in front of the two terms on the right-hand side. The recurrence equations can be solved analytically and the corresponding limits taken in the case a=1 \wedge b=1. They both involve the gamma function and some powers. The difference between the two “algorithms” is then that in the first, the gamma function is trivial while the power e^1 remains, while in the second, the power term calcels out with the factor 2 but the gamma function brings in \pi (as it often does). So the answer is no, these two sequences don’t disclose any commonalities between the two constants. They just evaluate to expressions which somehow contain both, and in either, one of the terms becomes trivial, leaving only the other.


Let’s solve the two systems in parallel (NB. the equations below come in pairs to show the correspondence, they are not systems.) Using the method of generating functions, we convert the equations
u_{n+2} &= a u_{n+1} + b\frac{u_n}n, \\
v_{n+2} &= a \frac{v_{n+1}}n + b v_n

with initial conditions u_1 = v_1 = 0, u_2 = v_2 = 1, to ordinary differential equations
\frac{f'(x)}x – \frac{2f(x)}{x^2} &= a\left(f'(x) – \frac{f(x)}x\right) + b f(x), \\
\frac{g'(x)}x – \frac{2g(x)}{x^2} &= a \frac{g(x)}x + b x g'(x)

f(x) &= \sum_{n=2}^{+\infty} u_n x^n, \\
g(x) &= \sum_{n=2}^{+\infty} v_n x^n.

The solutions for a>0, b>0 with a unit quadratic term (the initial condition) are
f(x) &= x^2 e^{-\frac{bx}a} (1 – a x)^{-1-\frac b{a^2}}, \\
g(x) &= x^2 (1 – \sqrt b x)^{-1 – \frac a{2\sqrt b}} (1 + \sqrt b x)^{-1 + \frac a{2\sqrt b}}.

We can extract the coefficients by writing down and expanding the Taylor series:
f(x) &= x^2 \sum_{k=0}^{+\infty} \frac1{k!} \left(\frac{-bx}a\right)^k \sum_{l=0}^{+\infty} \frac{(1+b/a^2)_l}{l!} (ax)^l \\
&\quad = \sum_{n=0}^{+\infty} \left[ \sum_{k=0}^n \frac{(-1)^k}{k!(n-k)!} \left(\frac ba\right)^k (1+b/a^2)_{n-k} a^{n-k} \right] x^{n+2}, \\
g(x) &= x^2 \sum_{k=0}^{+\infty} \frac{\big(1 + a/(2\sqrt b)\big)_k}{k!} (\sqrt b x)^k \sum_{l=0}^{+\infty} \frac{\big(1 – a/(2\sqrt b)\big)_l}{l!} (-\sqrt b x)^l \\
&\quad = \sum_{n=0}^{+\infty} \left[ \sum_{l=0}^n \frac{(-1)^l}{l!(n-l)!} \big(1 – a/(2\sqrt b)\big)_l \big(1 + a/(2\sqrt b)\big)_{n-l} (\sqrt b)^n \right] x^{n+2}.

The two expansions have some similarities and both allow us to write down and simplify (converting the Pochhammer symbols with negative k to positive k followed by using a straightforward application of the definitions, all doable in hand) the (n+2)-th coefficient:
u_{n+2} &= \binom{n+p}{p} a^n {}_1F_1(-n; -n-p; -p), \\
v_{n+2} &= \binom{n+q}{q} \sqrt b^n {}_2F_1(-n, 1-q; -q-n; -1),

where p and q are shorthand notation for the recurring subexpressions in either formula,
p &= b / a^2,\\
q &= a / (2 \sqrt b).

Now the similarity is quite striking (keeping in mind, however, that there’s a world of difference between _1F_1 and _2F_1, and between evaluation something in -1 and in a generic point), but that’s still not too surprising given how simple the original recurrent equations were.

We can find asymptotic forms of u_n and v_n from here. For that, it’s advantageous to rewrite the hypergeometrics so that the dependence on n appears only in the denominator terms. Here are two handy identities just for us: for the _1F_1 and for the _2F_1. This brings u_{n+2} and v_{n+2} to their equivalent forms
u_{n+2} &= \binom{n+p}{p} a^n e^{-p} {}_1F_1(-p; -n-p; p), \\
v_{n+2} &= \binom{n+q}{q} \sqrt b^n 2^{q-1} {}_2F_1(-q, 1-q; -q-n; 1/2),

Now as n \to +\infty, we are guaranteed that the _pF_q terms approach 1, so we can just trim them to the zeroth term each. For the generalized binomial coefficients, we use Stirling’s formula for the “big” factorials, leaving
\binom{n+\Delta}{\Delta} \approx \frac{n^\Delta}{\Delta!}.
This gives us the asymptotics
u_{n+2} &\approx \frac{a^n n^p e^{-p}}{p!}, \\
v_{n+2} &\approx \frac{\sqrt b^n n^q 2^{q-1}}{q!}.

As mentioned in the introduction, each of these terms has a geometric term and a gamma function (the factorial). They also have one exponential term each, which goes away for a=1 and for b=1, respectively:

For a=1, p=b and the asymptotic behaviour of u_{n+2} is
u_{n+2} \approx n^b e^{-b} / b!
and when compensated in a limit procedure, this tends to
\large \lim_{n \to +\infty} \frac{n^b}{u_n} = e^b b! = \Gamma(b+1) e^b.
In particular, b=1 gives the limit e^1 1! = e. For half-integer values of b, both e (in some power) and \pi (in a square root) will be present simultaneously.

For b=1, q=a/2 and the asymptotic behaviour of v_{n+2} is
v_{n+2} \approx n^{a/2} 2^{a/2 – 1} / (a/2)!
and when squared and compared to n^a, this gives the limit
\large \lim_{n \to +\infty} \frac{n^a}{v_n^2} = \frac{(a/2)!^2}{2^{a-2}} = \frac{\Gamma(1+\frac a2)^2}{2^{a-2}}.
In particular, a=1 produces \Gamma(3/2)^2 / 2^{-1}. Since \Gamma(3/2) = (1/2)! = \sqrt\pi/2, this is one half of \pi. The residual power of 2 is cancelled when the limit expression is {\bf 2}n / v_n^2. For a generic odd a, there would be some multiple of \pi and some power of 2.


Albeit the two equations can be solved using quite similar methods and even their full solutions share a lot of common features, the results e and \pi come ultimately from different and unrelated parts of the formulas. The former comes from a power term when all the other terms become trivial. The latter comes from a special value of a gamma function when the other terms are reduced to a constant of 2. The base e is connected to the properties of the Kummer function _1F_1 whereas the base 2 appears in a similar function for the Gauss function _2F_1.

Source : Link , Question Author : Yuriy S , Answer Author : The Vee

Leave a Comment